Plant‐parasitic nematodes of potential phytosanitary importance, their main hosts and reported yield losses. (16th July 2013) - Singh, S. K.; Hodda, M.; Ash, G. J.
<x xml:space="preserve">Abstract</x> The potential phytosanitary importance of all named plant‐parasitic nematode species was determined by evaluating available information on species characteristics, association with economically‐important crop hosts, and ability to act as vectors of viruses or form disease complexes with other pathogens. Most named species of plant‐parasitic nematodes (PPN) are poorly known, recorded from a single location only, not associated with economically‐important crops, and not known to be associated with other plant disease organisms. However, 250 species from 43 genera fulfilled one or more of the criteria to be considered to present a phytosanitary risk. The genera and number of species (in parentheses) considered as posing phytosanitary risk included: Achlysiella (1), Anguina (8), Aphasmatylenchus (1), Aphelenchoides (12), Aphelenchus (1), Belonolaimus (2), Bitylenchus (3), Bursaphelenchus (4), Cactodera (3), Ditylenchus (8), Dolichodorus (1), Globodera (3), Helicotylenchus (7), Hemicriconemoides (3), Hemicycliophora (3), Heterodera (25), Hirschmanniella (5), Hoplolaimus (5), Ibipora (3), Longidorus (10), Macroposthonia (2), Meloidogyne (38), Merlinius (3), Nacobbus (1), Neodolichodorus (2), Paralongidorus (2), Paratrichodorus (11), Paratylenchus (3), Pratylenchus (24), Punctodera (3), Quinisulcius (3), Radopholus (5), Rotylenchulus (3), Rotylenchus (1), Scutellonema (5), Sphaeronema (1), Subanguina (3), Trichodorus (5), Tylenchorhynchus (8), Tylenchulus (2), Vittatidera (1), Xiphinema (15) and Zygotylenchus (1). For each of the 250 species main hosts and yield loss estimates are provided with an extensive bibliography. Of the 250 species, only 126 species from 33 genera are currently listed as regulated pests in one or more countries worldwide. Almost all of these 250 species were also associated with economically important crops and some also acted as vectors for viruses.